Undrained shear and pore space characteristics of treated loose sands with lime-activated zeolite in saturated settings - Jamhiri, Babak; Pakbaz, Mohammad Siroos (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This research investigates the mechanical behavior of artificially cemented sandy soils formed by lime alkali activation of natural zeolite under saturation settings. In order to verify the bar capability of cemented sands with this new method, an analysis of the undrained shear strength of the soil with pore water pressure ratio measurements was performed from the interpretation of the results of unconfined compression tests. The effect of zeolite-lime blend on treated sands was also visualized by scanning electron microscopy.
Keywords: lime alkali; compressive strength; shear strength; void ratio; pore water pressure; B-ratio; wapno alkaliczne; wytrzymałość na ściskanie; wytrzymałość na ścinanie; ciśnienie wody